2022
DOI: 10.1080/19490976.2022.2143225
|View full text |Cite
|
Sign up to set email alerts
|

Morphine mediated neutrophil infiltration in intestinal tissue play essential role in histological damage and microbial dysbiosis

Abstract: The gut microbial ecosystem exhibits a complex bidirectional communication with the host and is one of the key contributing factors in determining mucosal immune homeostasis or an inflammatory state. Opioid use has been established to induce gut microbial dysbiosis consistent with increased intestinal tissue inflammation. In this study, we investigated the role of infiltrated immune cells in morphine-induced intestinal tissue damage and gut microbial dysbiosis in mice. Results reveal a significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
6
1
Order By: Relevance
“…Of note, Coriobacteriaceae UCG-002 , Butyricimonas , Parabacteroides , Ruminococcaceae UCG-010 , and Ruminococcaceae UCG-014 are known to produce SCFAs, primarily propionate and butyrate. , Moreover, the relative abundances of Enterococcus , Lachnospiraceae NK4A136 group , and Escherichia-Shigella were noticeably diminished by YS108R EPS treatment. Enterococcus , a well-studied pathogenic genus, impairs the intestinal epithelial barrier through disruption of TJ function, becoming a contributor to gut inflammation, and is heavily enriched in patients with intestinal diseases, such as CRC and CD . A study suggested that UC mice were accompanied by a decrease in the relative abundance of Lachnospiraceae NK4A136 group , which was contrary to our findings, however, it has also been reported that Lachnospiraceae NK4A136 group showed a significant inverse association with SOD and T-AOC, but a positive association with MDA …”
Section: Discussioncontrasting
confidence: 99%
“…Of note, Coriobacteriaceae UCG-002 , Butyricimonas , Parabacteroides , Ruminococcaceae UCG-010 , and Ruminococcaceae UCG-014 are known to produce SCFAs, primarily propionate and butyrate. , Moreover, the relative abundances of Enterococcus , Lachnospiraceae NK4A136 group , and Escherichia-Shigella were noticeably diminished by YS108R EPS treatment. Enterococcus , a well-studied pathogenic genus, impairs the intestinal epithelial barrier through disruption of TJ function, becoming a contributor to gut inflammation, and is heavily enriched in patients with intestinal diseases, such as CRC and CD . A study suggested that UC mice were accompanied by a decrease in the relative abundance of Lachnospiraceae NK4A136 group , which was contrary to our findings, however, it has also been reported that Lachnospiraceae NK4A136 group showed a significant inverse association with SOD and T-AOC, but a positive association with MDA …”
Section: Discussioncontrasting
confidence: 99%
“…In particular, metabolic changes in morphine-tolerant mice were mitigated, raising the question of whether changes in the plasma metabolites following acute morphine intake were contributing to morphine analgesic effects and whether they could serve as tolerance indicators. The role of metabolic changes in morphine-mediated pathologies [ 43 , 51 , 52 , 53 , 54 , 55 ] demands additional studies. Our findings warrant further investigation in other morphine tolerance models and humans.…”
Section: Discussionmentioning
confidence: 99%
“…This activation could potentially occur via direct downstream signaling of the μ‐opioid receptor, 85 as well as via the activation of the TLR‐4 signaling pathway, binding to the adaptor molecule MD‐2, within the central nervous system 25,86 . Recent studies have described the role of morphine to induce peripheral inflammation, specifically by inducing dysbiosis and amplifying bacterial translocation from the intestine to the liver and mesenteric lymph nodes 87–89 . This cascade of events potentially triggers a systemic pro‐inflammatory state, 90,91 thereby underscoring a new mechanism of action in opioid dependence that merits further exploration.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 86 Recent studies have described the role of morphine to induce peripheral inflammation, specifically by inducing dysbiosis and amplifying bacterial translocation from the intestine to the liver and mesenteric lymph nodes. 87 , 88 , 89 This cascade of events potentially triggers a systemic pro‐inflammatory state, 90 , 91 thereby underscoring a new mechanism of action in opioid dependence that merits further exploration. These findings highlight the complex interplay among opioid addiction, secretome treatment, and neuroinflammation, providing information for future studies to evaluate these mechanisms.…”
Section: Discussionmentioning
confidence: 99%